Which Side Are They On? Thinking About The Labour Bureaucracy - Leier, Mark (James Mark) (Labour / Le Travail, 1996)
The article reviews and comments on the books, "Hoffa," by William Sloane, and "Labor Shall Rule: Sidney Hillman and the Rise of Labor," by Steven Fraser.
Keywords: BOOKS -- Reviews; FRASER, Steven; HOFFA (Book); LABOR Shall Rule: Sidney Hillman & the Rise of Labor (Book); Nonfiction; SLOANE, William, 1906-1974